"The Sinusoid" in the Liver: Lessons Learned from the Original Definition by Charles Sedgwick Minot (1900). Issue 12 (28th September 2015) - Wake, Kenjiro; Sato, Tetsuji
ABSTRACT: The hepatic sinusoid with its associated sinusoidal cells is a multifunctional cell‐complex in the liver. Despite recent advances in research on the hepatic sinusoid, no investigator has played a more basic role in its characterization than Charles Sedgwick Minot (1852–1914), a pioneer who distinguished the sinusoid from the blood‐capillary as early as 1900. According to Minot, sinusoids are typically larger in diameter than capillaries, particularly at the early embryonic stage. They closely approach the parenchymal tissue, are formed passively by the adjacent parenchymal tissue, and are on rare occasion surrounded with connective tissue. Sinusoids (sinus‐like) are small blood‐channels formed by subdivision of the lumen of large blood vessels (sinuses) by the invasion of developing parenchymal cell‐cords. Although some of Minot's definitions may no longer be accepted, he described some fundamental and interesting characteristics of sinusoids, to which we have not paid much attention. Here, we have attempted to illustrate lessons we have learned from Minot's view point of sinusoids at this occasion of centenary of his death. Anat Rec, 298:2071–2080, 2015. © 2015 Wiley Periodicals, Inc.